2019
DOI: 10.1111/jzo.12746
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal factors impacting encounter occurrences between leopards and other large African predators

Abstract: Encounters between individuals can have implications for a range of processes, including disease transmission, information transfer and competition. For large carnivores, difficulties in directly observing individuals and historical hardware limitations of GPS collars mean that relatively little is known of the spatio‐temporal factors contributing to encounters. The African large predator guild represents one of the few remaining functionally intact guilds of large carnivores on the globe and so represents a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Whilst dietary niche separation may be one mechanism through which competition is avoided (Du Preez et al , 2017), co‐occupation of shared habitat patches may also be facilitated by aspects of the leopard’s life history that, in comparison to other guild species, make them particularly well suited to coexistence within these areas, with avoidance of competitor encounters then occurring at a finer spatial scale (e.g. Rafiq et al , 2019). For example, leopards are a cryptic and solitary species and so may be able to maintain a relatively low risk of detection by dominant competitors whilst moving through shared areas (Bailey, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst dietary niche separation may be one mechanism through which competition is avoided (Du Preez et al , 2017), co‐occupation of shared habitat patches may also be facilitated by aspects of the leopard’s life history that, in comparison to other guild species, make them particularly well suited to coexistence within these areas, with avoidance of competitor encounters then occurring at a finer spatial scale (e.g. Rafiq et al , 2019). For example, leopards are a cryptic and solitary species and so may be able to maintain a relatively low risk of detection by dominant competitors whilst moving through shared areas (Bailey, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Du Preez et al , 2015; Miller et al , 2018), despite the fact that leopards co‐occur and compete with other guild members across their African range. As such, relatively little is known of spatio‐temporal interactions involving leopards and other members of the guild (but see Vanak et al , 2013; Rafiq et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This dense vegetation structure creates a kind of visibility hindrance; consequently, less interference encounters between leopard and lion. Recently, Rafiq et al [47] have also reported that leopard and lion encounters occurred less in dense habitat due to visibility obstruction. Balme et al [22] have also termed such habitats as "hideable habitat" for leopards, which act as a refuge for them to avoid a dominant member of the guild.…”
Section: Plos Onementioning
confidence: 99%
“…Localized extirpation of lion populations is expected to increase over the coming decades, with the species predicted to survive in only the largest protected areas across Africa and in small, intensively managed, reserves (Bauer et al., 2015). Consequently, understanding carnivore dynamics in areas of anthropogenic disturbance is important for predicting future alterations in carnivore guilds (Rafiq, Jordan, Wilson, et al., 2020). The intraguild dynamics of leopard and hyena in KNP can, therefore, act as a model to inform conservation management under increasing levels of environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…Leopards also exhibit behavioral adaptations (i.e., tree caching and dietary plasticity) to facilitate coexistence with hyena (Balme et al., 2019; Briers‐Louw & Leslie, 2020). However, the spatiotemporal dynamics of leopard and hyena are often overlooked (Rafiq, Jordan, Wilson, et al., 2020; Vanak et al., 2013), particularly in ecosystems where the carnivore guild has been depleted due to anthropogenic disturbance. The lack of understanding of coexistence strategies between leopard and hyena in such areas limits conservation management.…”
Section: Introductionmentioning
confidence: 99%